Glasnost, perestroika, and U. S. defense spending - Kaufmann, William W. (Washington D. C. The Brookings Institution, 1990)
In this timelt book, Kaufmann proposes a plan to cut defense spending by almost half over the next decade. He explains that an adjustment of spending plans is essential: the Soviet Union has already begun to reduce its conventional forces, as have other members of the Warsaw Pact, and Moscow is now willing to accept parity in nuclear and conventional capabilities at reduced levels.
Keywords: Politics